Utilidad del Polietileno Tereftalato (PET) y Polipropileno (PP) reciclado, para la fabricación de monturas oftálmicas (2023)
The present work aims to evaluate the usefulness of Polyethylene Terephthalate (PET) and Polypropylene (PP) recycled for the manufacture of ophthalmic frames. Ophthalmic frames are a mechanical support for optical systems such as lenses, prisms and filters, which must meet certain mechanical and hypoallergenic for clinical use. It should be noted that these properties mechanical and hypoallergenic although they are mentioned by the Icontec 5607 standard are not well defined in practice